Convenient synthesis of hollow tubular In2O3/PDA S-scheme inorganic/organic heterojunction photocatalyst for H2O2 production and its mechanism - Yunhao Ma; Shan Wang; Yingjie Zhang; Bei Cheng; Liuyang Zhang (Journal of Materiomics)
The development of heterojunction photocatalysts for hydrogen peroxide (H2O2) generation is both environmentally sustainable and cost-effective but presents considerable challenges. In this study, we synthesized hollow tubular indium oxide (In2O3) by calcining In-MIL-68 and subsequently composited it with polydopamine (PDA) via in-situ self-polymerization. This process resulted in the formation of an In2O3/PDA step-scheme (S-scheme) heterojunction. The optimized sample demonstrated H2O2 production rates approximately 2.1 and 4.5 times higher than the pure In2O3 and PDA, respectively. The enhanced photocatalytic performance of the In2O3/PDA composite is the result of several synergistic factors: increased light absorption due to the hollow structure, a larger specific surface area, and high separation efficiency of photo-generated electron-hole pairs facilitated by the S-scheme heterojunction. In-situ irradiated X-ray photoelectron spectroscopy (ISI-XPS) confirmed the charge transfer pathway follows the S-scheme mechanism. This work not only highlights a practical method for constructing inorganic/organic S-scheme heterojunction photocatalysts but also provides a detailed analysis of their underlying mechanisms, paving the way for more efficient and sustainable photocatalytic systems.